2022
DOI: 10.37741/t.70.3.9
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Covid-19 on the Tourism Sector

Abstract: This exploratory study charts the transformation of the tourism sector caused by the COVID-19 crisis. The article dissects five key domains of industry transformation: accelerated digitalisation, business model flexibility, human resources, travel restrictions, and risk perception and crisis management. It delineates the industry's changes, adaptations, and associated challenges in each domain. A review and content analysis of 240 publicly available online documents was conducted. The results provide manageria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…The increase in local travel accelerated the supply of services related to such travel, while the restrictions on movement applied during the quarantine encouraged the creation of more diverse tourism products, and also contributed to the digitization of the sector and the growth of virtual travel. Similar trends are observed by other authors (Brozović & Saito, 2022). All these newly developed products would undoubtedly accelerate the recovery and further development of the…”
Section: Discussionsupporting
confidence: 88%
“…The increase in local travel accelerated the supply of services related to such travel, while the restrictions on movement applied during the quarantine encouraged the creation of more diverse tourism products, and also contributed to the digitization of the sector and the growth of virtual travel. Similar trends are observed by other authors (Brozović & Saito, 2022). All these newly developed products would undoubtedly accelerate the recovery and further development of the…”
Section: Discussionsupporting
confidence: 88%
“…In conclusion, the COVID-19 pandemic significantly highlighted several emerging issues in tourism worldwide (Brozović & Saito, 2022). Tourist behavior and travel intention post-pandemic became essential issues, especially when tourists perceive risks in the destination.…”
Section: Discussionmentioning
confidence: 95%
“…The COVID-19 crisis has occurred alongside significant societal and technological transformations, which have further complicated the challenges the tourism sector faces. These transformations include the digitization of the industry, increased competition for hosting meetings, evolving lifestyles, and societal movements such as Flygskam (Flight shame) that highlight the importance of sustainability (Christofle, 2021;Brozović & Saito, 2022).…”
Section: Congress Tourism and The Covid-19 Crisismentioning
confidence: 99%
“…The crisis has not been explored, and its contemporary consequences have been on the congress system, stakeholders, and territories (Lončarić et al, 2022). Therefore, it is crucial to examine the shock absorption measures implemented by international congress tourism stakeholders in response to the pandemic crisis and assess whether they acted with agility (Kalaignanam et al, 2021) or demonstrated innovative approaches in line with the global transformation of the sector (Gössling et al, 2020;Brozović & Saito, 2022), including digitization and an increased emphasis on sustainability principles (Brozović & Saito, 2022;Christofle, 2023;Morrison & Coca-Stefaniak, 2023).…”
Section: Introductionmentioning
confidence: 99%